A Review of the Dimroth Rearrangement in Fused 1,2,4-Triazolo[4,3-c]pyrimidines - Rashad, Aymn E.; Abdel-Megeid, Farouk M.E.; Abdel-Megid, Mohamed; El Malah, Tamer; Shamroukh, Ahmed H. (Current Organic Chemistry, 2026)
Dimroth rearrangement is a type of molecular rearrangement involving the interconversion of triazoles under acidic or basic conditions. It is particularly significant in heterocyclic chemistry, and it involves the migration of substituents around the nitrogen atoms in the ring system. This review concerns the formation of fused five-membered 1,2,4-triazolo[4,3-c]pyrimidines from their corresponding 4-hydrazinopyrimidine derivatives. Additionally, it discusses their Dimroth-type rearrangement into the thermodynamically more stable 1,2,4-triazolo[1,5-c]pyrimidine isomers under various reaction conditions. Moreover, it was observed that the presence of an acid, base, and aliphatic substituents in C3 and C5 of triazolo[4,3-c]pyrimidine structure facilitates the Dimroth-type rearrangement. In general, the two isomeric series differ significantly in their melting points, proton NMR chemical shift positions, and UV absorption wavelengths.
Keywords: 1; 2; 4-Triazolo[1; 5-c]pyrimidines